(3EOGQI GdeYQaI hYdGbJgG HGdUMI hGdSdGeI GdegfjI ddeQTOjf GdRQGYjjf HHYV eMGaXGJ L(B.(3e(B.(3Ys - (3YHO GdMdje, MfGf ceGd s; (3fGUQ, YHO GdZfi eMeO YHO GdOGje(B.s; (3GdSjO, WGQb eMehO CMeO(B.s (2015)
(3GSJgOa gPG GdMK JMOjO eSJhi EOGQI GdeYQaI OGNd GdEQTGOi GdRQGYi, hCge eNGWQ hCeQGV GdYed GdJi jJYQV dgG GdeQTOhf GdRQGYjhf GdeHMhKhf, hJLjO eSJhi JhaQ YhGed GdCeGf ddeHMhKjf HGdYed,s
(3jMJhi Ydi eQGLY(B.s
(3edNU HGddZI GdCfLdjRjIs
1
Keywords: (3GdEQTGO GdRQGYis -- (3JOQjH(B.s; (3GdeQTOhf GdRQGYjhf(B.s; x